2011
DOI: 10.1074/mcp.m110.006916
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Serodiagnostic and Subunit Vaccine Antigens by Antibody Profiling of Toxoplasmosis Cases in Turkey

Abstract: Toxoplasmosis, caused by infection of the protozoan parasite Toxoplasma gondii, is associated with mild disease in healthy individuals, whereas individuals with depressed immunity may develop encephalitis, neurologic disorders, and other organ diseases. Women who develop acute toxoplasmosis during pregnancy are at risk of transmitting the infection to the fetus, which may lead to fetal damage. A diagnosis is usually confirmed by measuring IgG, or IgM where it is important to determine the onset of infection. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 64 publications
2
56
0
1
Order By: Relevance
“…Owing to the small volumes of sera required to probe arrays and the ease with which they can be screened in a high-throughput fashion, the array platform is ideal for seroepidemiological studies against hundreds of pathogen antigens simultaneously (20,31,49,52). Seroprevalence of HSV is influenced by age, sexual activity, and ethnicity, and a much larger study would be required to estimate seroprevalence in the United States properly using the array platform.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the small volumes of sera required to probe arrays and the ease with which they can be screened in a high-throughput fashion, the array platform is ideal for seroepidemiological studies against hundreds of pathogen antigens simultaneously (20,31,49,52). Seroprevalence of HSV is influenced by age, sexual activity, and ethnicity, and a much larger study would be required to estimate seroprevalence in the United States properly using the array platform.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liang et al (2011) identified several antigens for detection of IgM antibodies using protein microarray displaying the polypeptides products of Toxoplasmic exons with well-characterized sera. Usually, IgM antibodies are generated within a week after infection, reaching a peak, and then rapidly decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides can be arranged in microarrays, thus allowing simultaneous analysis of up to several thousands of peptides with a single serum sample. With this technique, global patterns of antibody responses to various infectious agents were studied (3,35,36,42,44).…”
mentioning
confidence: 99%